The Function of Large Vessels in Normal-Weight and Overweight Children With Psoriasis During Methotrexate Therapy - Nikolay N. Murashkin; Olga V. Kogevnikova; Alexander I. Materikin (Педиатрическая фармакология, 2019)
Background. In recent years, the opinion has been established that skin manifestations of psoriasis are associated with the damage of other organs and systems, and that psoriatic lesions have a systemic nature, and therefore the term ‘psoriatic disease’ is increasingly used in scientific literature. Among psoriasis comorbidities, metabolic disorders and cardiovascular diseases are of particular clinical importance. Our aim was to study the effect of systemic cytostatic therapy with methotrexate on the remodelling processes of large vessels in children with psoriasis who have normal and increased body mass index. Methods. The primary data was collected by extracting data from medical records and case follow-up records. The subsequent accumulation, storage, grouping and primary sorting of research data were carried out using a personal computer and Excel application package. Clinical evaluation of the severity of psoriasis and skin lesions was assessed by calculating the PASI index. Non-invasive oscillometric arteriography was performed on a portable ArterioGraph (TensioMed Ltd, Hungary). Results. A direct significant correlation has been established between the revealed impairments of the function of large arteries and the indicators of fat metabolism, the severity of psoriasis and body mass index. During the systemic pathogenetic cytostatic therapy with methotrexate, a significant positive dynamics of the function parameters of large arteries was revealed in children with psoriasis who have both normal and increased body mass index. Conclusion. The undertaken studies showed that methotrexate is an effective and safe agent for treating psoriasis in children aged from 3 to 18 years, has a positive effect on the function of large vessels.Nikolay N. Murashkin — receiving research funding from pharmaceutical companies Jansen, Eli Lilly. Receiving fees for scientific advice from Galderma, Pierre Fabre, Bayer, Astellas, Libriderm.Alexander I. Materikin — receiving research funding from pharmaceutical company Eli Lilly. Receiving fees for scientific advice from Bioderma, Libriderm.